CHARACTERIZATION OF THE OPERATIONAL SYSTEMS, MODALITIES AND FISHING ARTS USED FOR THE CATCH OF THE LOBSTER PANULIRUS GRACILIS (STREETS, 1871) IN GUANACASTE, COSTA RICA - Naranjo-Madrigal, Helven (2010)
We describe two fishing methods used in the fishery for the Pacific spiny lobster Panulirus gracilis (Streets, 1871) in Santa Cruz, Guanacaste, Costa Rica, which include lung diving and “hookah” diving (using a compressor) associated with a single gear called “bichero”. This fishing gear is unique in being extremely versatile as it allows capturing other species of commercial interest. However, the use of this gear under water with the “hookah” fishing modality could potentially cause lobster dispersal and affect lobster growth, and also leaves the size selectivity as a decision that has to be made by fishermen. It also describes the equipment used in both fishing styles, as well as how they operate and the physical risks posed by “hookah” for fishermen. Furthermore, we recommended other types of selective fishing gear, whereas traditional